Effectiveness of Adjuvant Treatment of N-Acetylcysteine on Negative Symptoms and Neutrophil-Lymphocyte Ratio (NLR) in Schizophrenic Patients - Ranto, Ipak; Herdaetha, Adriesti; Kusuma, Wijaya (Universitas Airlangga, 2023)
Highlights:1. The essence of schizophrenia is the negative symptoms.2. Adding meloxicam can improve the negative symptoms and changes in the NLR in schizophrenic patients. AbstractIntroduction: Schizophrenia is a mental disorder that has a negative symptom domain. Negative symptoms are commonly referred to as the essence of schizophrenia. Treatment of negative symptoms is still considered less than optimal. The ratio of neutrophils and lymphocytes is one of the markers of inflammation. This study aimed to analyze the effectiveness of N-acetylcysteine as adjuvant therapy for improving negative symptoms and changes in the neutrophil-lymphocyte ratio (NLR) in schizophrenic patients. Methods: This was a quasi-experimental study using a single-blind, pretest–post-test design. The subjects were 34 schizophrenic patients who were inpatients at Dr. Arif Zainuddin Regional Mental Hospital (RSJD), Surakarta, from May to July 2020. The subjects were assigned using a purposive sampling technique based on inclusion criteria and received adjuvant N-acetylcysteine therapy at 400 mg/day for 4 weeks. Data collection was obtained from medical records, interviews, field notes, positive scale, negative scale, and general psychopathology scale (PANSS) assessment sheets, and blood NLR examinations. Data analysis used SPSS 25.0.Results: There was a significant difference between the treatment and control groups in reducing negative PANSS subscale measurement after adjuvant N-acetylcysteine treatment. However, there was no significant difference between the control and treatment groups after N-acetylcysteine administration for NLR.Conclusion: The dose of adjuvant therapy N-acetylcysteine given to patients in this study had an effect on decreasing the negative subscale PANSS score.